ALUMINA RECOVERY FROM SOLID WASTE SLUDGE (SWS) PDAM BANJAR INTAN - Sari, Retno Fitriana; Prasetyo, Winda Aryani; Mirwan, Agus (Universitas Lambung Mangkurat, 2017)
Abstract- Solid Waste Sludge (SWS) PDAM are formed by deposition of solid particles in water that has been given a coagulant such as alum and PAC (Poly Aluminum Chloride). SWS PDAM have the content of alumina (Al2O3) is quite high, making it possible to get alumina by recovery process. This research aims to study the process of recovery of alumina from SWS PDAM and determine the condition of the process to obtain optimum alumina.The process of recovery of alumina from a material divided into three main processes. First process was calcination material to break the complex bonds aluminosilicate contained in the material, in which some compound was added before calcination and to used to bind the compound alum. The second process is the solid-liquid extraction (leaching) that serves to separate the silica and alumina. Silica will precipitate and alumina will dissolve. Next process is the decomposition of hydrolysis, the compound of Al will be heated by adding water so that the hydrated form of alumina.This research was conducted with several stages. First SWS PDAM is mixed with CaCl2, by variation ratio of CaCl2:SWS PDAM are 0,5:1, 1:1 and 1.5:1, then calcined at temperature of 800oC. Calcined particle with size 200 mesh was leached by HCl with variation concentration of 4M, 6M and 8M. Solution was added to 100ml of water and heated to 100ml left. Results were analyzed asÂ %w / w alumina contained in the solution. The results of the best variations made to the recovery of alumina in this study is to use a variation of weight ratio 1:1 CaCl2 and SWS PDAM with HCl concentration on the leaching process of 8M obtained alumina recovery percentage 15.68%. Key words: alumina, SWSÂ PDAM, calcination, leaching.